Group Communication in The Brigade Joxzin Community Organization in Maintaining Group Cohesivity During The COVID-19 Pandemic - Ramadhana, Muhammad Biondy; Suciati, Suciati (Jogjakarta Communication Conference (JCC), 2023)
This research was reduced to the form of group communication found in the Brigade Joxzin group during the Covid pandemic, which was a forum for sympathizers of the Partai Persatuan Pembangunan (PPP). During its establishment, members of the Brigade Joxzin experienced an increase in the number of members and have survived to this day. This study uses a descriptive qualitative research method. The data collection techniques used are interviews, observation, and documentation. After obtaining the required data, the researcher will analyze the data by carrying out the process of collecting data, reducing data, and then conducting discussions to get the conclusions needed. The results of this study prove that the form of group communication within the Brigade Joxzin group during the Covid pandemic still worked as it should. The relationship between members feels close to each other like family, and all members contribute significantly; interactions are often carried out both online and offline, social media is always used actively, and personal chat is usually established. The topics discussed at the meeting are also private. When a new member is considered like a new family, internal and external activities are carried out together, using community attributes and solving internal problems. When there are threats from outside, together will resolve either in the family or even brought to justice.